Solving multi level multi-objective linear programming (ML MOLP) problems with fuzzy parameters (FPs) - Babić, Zoran; Hunjak, Tihomir; Perić, Tunjo (Croatian Operational Research Review, 2023)
Making numerous business decisions in complex decentralized organizations can be presented as a ML MOLP problem with FPs expressed as triangular fuzzy numbers. This paper presents a methodology that uses several multi-objective programming methods to solve this problem. The Iskander’s method was used for defuzzification of the objective functions and constraints of the problem and a multi-objective programming method based on the cooperation among decision makers was used to determine the aspired values of the variables controlled by the decision-makers and to obtain the preferred non-dominated solution of the entire problem. The efficiency of the proposed methodology was tested on an example of production planning in a complex decentralized company.